Uso de diferentes agentes ligantes no desenvolvimento de barra de cereal salgada adicionada de chia (Salvia hispânica L.) - Tramujas, Janaína Melati (2015)
The objective of this study was to evaluate different binders when preparing salt cereal bars and to characterize them as physical, physico-chemical and sensory parameters. Four formulations of different cereal bars using binders have been developed. The evaluated binders were collagen, guar gum, xanthan gum and psyllium. The developed cereal bars were evaluated according to their physical characteristics (color and texture), physicochemical (pH, moisture, ash, protein, lipids, Aw, crude fiber) beyond their calorie, fatty acid composition and concentration of the main minerals. Among the four binding agents evaluated, psyllium stood out due to its physicochemical characteristics. A cereal bar high in protein and fiber; low in carbohydrates and water activity. The binding agent guar gum and xanthan showed characteristics similar to psyllium, especially regarding to fiber content. Collagen as binder gave the final product a high level in protein and lipid. The color and texture analyzes showed that the salt cereal bars had the color and crispness characteristics for this type of product. Regarding to the composition in the fatty acid, the developed bars offer a good supply of essential fatty acids to the human body. The same was observed regarding to mineral contents. Sensory, salt cereal bars made with chia showed good acceptability, highlighting the elaborate bar with psyllium binder. Different binders demonstrated technological efficiency in the preparation of salt cereal bars. The binder psyllium agent over others showed better physical-chemical and sensory characteristics. However, in general the product has healthy and nutritional characteristics it may be indicated for a protein diet with high fiber content and free sugars.